UJI DAYA HAMBAT EKSTRAK BATANG Harrisonia perforata (Blanco) MERR. TERHADAP PERTUMBUHAN BAKTERI Streptococcus mutans - Sa’adia Alydrus; Orryani Lambui; Ramadhanil Pitopang (Biology Department, Mathematics and natural science, Tadulako University, 2016)
The research about inhibition test of stem extract of Harrisonia perforata (Blanco) Merr. to the growth of Streptococcus mutans had conducted diving period of February to March 2015. The aim of this research was to study the inhibition test from stem extract plant of H. perforata (Blanco) Merr. on the bactery studied. The extraction was used reflux method.The experiment was arrenged in Completely Randomized Designed (CRD) with 5 treatments and 3 repititions. The treatments were stem extract concentrates 40%, 50% and 60%, positive control Tetrasiklin hidroklorida 2% and negative control Na-CMC 1%. The result showed that stem extract of H. perforata (Blanco) Merr. had inhibition effect to the growth of bacteria. The extract concentrations 60% produced the biggest inhibition zone for S. mutans 21,4 mm than other concentrations. Keyword : Stem extract of Harrisonia perforata (Blanco) Merr., Streptococcus mutans.